Analysis of Squid (Loligo sp.) Utilization and Sustainable Management Strategies in The Water of North Sulawesi Province, Indonesia - Talitha Zerlinda Gunawan; Anaya Noveleta; Dianatalia; Elsa; Paraning Gita Cahyani; Sudirman Adibrata; Lizha Dwi Mulya Putri (Yayasan Serumpun Karang Konservasi, 2025)
This study aims to analyze the utilization status of squid (Loligo sp.) resources and formulate sustainable management strategies in North Sulawesi Province, Indonesia. The study was conducted in May 2025 in the waters of North Sulawesi Province, which are part of the Indonesian Fisheries Management Area (IFMA) 715. A quantitative descriptive method was employed, using secondary data obtained from reports published by the Ministry of Marine Affairs and Fisheries, capture fisheries statistics, and relevant scientific literature. The data analyzed include squid (Loligo sp.) catch production, the number of squid (Loligo sp.) fishing gears, and the estimated Allowable Catch (TAC) for the years 2020–2024. The research results indicate that squid (Loligo sp.) production has experienced fluctuations, with the highest production in 2024 at 1,933.21 tons, still below the TAC value of 2,712 tons; however, the utilization rate has approached the optimal limit. The relationship between the number of fishing gear and production shows a negative pattern influenced by environmental factors, seasons, and resource stock conditions. The recommended management strategies include the implementation of the Ecosystem Approach to Fisheries Management (EAFM), control of fishing effort, limitation of fishing gear, and the use of environmentally friendly fishing technology to ensure the sustainability of squid (Loligo sp.) resources in the water of North Sulawesi Province.